3-Phase Multi-Functional Grid-Tied Inverter for Compensation of Oscillating Instantaneous Power - Olimpio Filho, Jose de Arimateia [UNESP]; Paredes, Helmo Kelis Morales [UNESP]; Santos Alonso, Augusto Matheus dos; Bonaldo, Jakson Paulo; Marafao, Fernando Pinhabel [UNESP]; Simoes, Marcelo Godoy; Batschauer, A. L.; Filho, AJS; Rech, C.; Brandao, D. I.; Martins, D. C.; Tedeschi, E.; et al. (Ieee, 2019)
The primary objective of this paper is to present the basic terms of Conservative Power Theory (CPT) and its applications for compensating instantaneous power oscillations in three-phase three-wire systems. The reference signals for a three-phase multi-functional grid-tied inverter are derived using the instantaneous power and the instantaneous reactive energy terms defined by CPT, having the oscillating power components defined directly in a-b-c coordinates. The compensation method proposed in this study is validated through simulations based on practical power system modeling. The results presented here show the feasibility and singularities of the proposed method.
Keywords: Conservative Power Theory; Instantaneous Power Oscillations; Multifunctional Grid-Tied Inverters; Power Quality; Renewable Energy Sources